Comment on Salva Shariq, et al. (J Pak Med Assoc. 2024; 74: 602) The potential of methylene blue in treating septic shock: is it worth a shot? - Afnan Amjad; Faraz Mansoor (Journal of the Pakistan Medical Association, 2024)
We read with interest the letter to the editor titled “The potential of methylene blue in treating septic shock: is it worth a shot?”.1 There is no doubt that septic shock is associated with a very high mortality and it is one of the most common indication for patients admitted to the medical intensive care units. It is important for the clinicians to understand that the most common causes of sepsis include Pneumonia, intra-abdominal sepsis, meningitis and urinary tract infection which require appropriate antibiotics as early as possible and fluid resuscitation, and vasopressors support as needed. Continune....